Expecation Gap in Surabaya: The Assessment Between Auditors With Audit Report Users - Wibowo, Danny (Future Science, 2021)
Expectation gaps always occur in companies where there is a difference between what public accountants (auditors) believe to be their responsibilities and what users of financial statements want. Thus this study discusses the expectation gap which aims to determine the performance of auditors in performing any audit work, to know the reactions of audit report users when reading the audit results, and to find out the process between auditors and audit report users when experiencing an expectation gap. This assessment uses qualitative data types. Sources of data used are observation and interviews. This research uses descriptive research and data analysis used is descriptive qualitative analysis. In this study, there is a conclusion that there are differences in expectations between auditors and auditees. Factors that trigger differences in expectations include; audit education both on the auditor and the auditee side, the standards owned by the auditor, the auditor's performance and the auditor's experience and the auditee's attitude